Transfer of Avatar Training Effects to Investigative Field Interviews of Children Conducted by Police Officers - Kask, Kristjan; Pompedda, Francesco; Palu, Annegrete; Schiff, Karolyn; Mägi, Mari-Liis; Santtila, Pekka (Frontiers in Psychology, 2022)
Previous research with students and some professional groups (psychologists) have repeatedly demonstrated that repeated feedback in simulated investigative interviews with computerized child avatars improves the quality of the interviews conducted with real children who have witnessed a mock event. However, it is not known whether the avatar training effects would transfer to investigative interviews with real child victims or witnesses of physical and sexual abuse conducted by police investigators. Twenty two police investigators participated in the study. Half of the participants first received no feedback and then received feedback (control group) while the other half received feedback (experimental group) on their performance during repeated interviews with avatars. Investigators were asked to present a transcript of an interview with a real child victim or witness prior the avatar training and also after the avatar trainings (control group had to present two transcripts, experimental group one transcript). Providing feedback to the avatar training increased the proportion of recommended questions both in avatar interviews as well as interviewing with real child victims and witnesses of sexual and physical abuse. The transfer effect of knowledge to practice was demonstrated by the first time in a sample of police investigators.